Government Strategy to Increase the Productivity of MSMEs in Bumi Aji Village, Batu City - Cicilia Evie Dawantara; Octa Dwi Sofian; Klara Kumalasari; Nurhayati Asegaf; Eka Agustiningtias (CV. Austronesia Akademika, 2024)
MSMEs in the national economy have a role as the main actors in economic activities. Micro, Small and Medium Enterprises (MSMEs) as a concrete player in the people's economy feel a strategy to be developed, because this sector is able to provide employment opportunities that are able to absorb the expected high workforce. The aim of this research is to examine local government strategies in increasing the productivity of MSMEs in Bumi Aji village, Batu city. The research method used in this research uses an exploratory descriptive type with a qualitative approach. The results of the research are the Petama Department of Small and Medium Enterprise Cooperatives and the Department of Industry and Trade which are the technical implementers in empowering MSMEs for processed mangoes. Second Resource development. Third, capital facilitation, fourth, expanding market access, fifth, facilitation of establishment permits, sixth, capital facilitation for MSMEs is regional bank loans, apart from that there are several other facilities, namely through the provision of Working Capital Credit, CSR. The strategy to expand market access is carried out, among others, through exhibition events at local, regional and national levels, printed (and electronic) media as well as the implementation of regulations regarding the requirements for establishing a mini market business, there must be five local MSME products. The next strategy is for the Batu City Government to provide socialization about the GAH MSME partnership. for all business information. Eight strategies for improving MSMEs in Batu City by creating an electronic catalog is a system in the form of lists, types, technical specifications, prices of goods, which are set out in a list and are easily accessible digitally